ANALYSIS OF RURAL TRANSFORMATION TRAJECTORIES IN THE POST-SOVIET SOCIETY: A SPOTLIGHT ON DAGESTAN - Linar Imangulov; Sergey Safronov; Maria Savoskul (Zbornik Radova: Geografski institut "Jovan Cvijić")
The article analyzes the spatial features of the post-Soviet socio-economic transformation of rural areas of southern Russia with the Republic of Dagestan as an example. The limited availability of reliable statistical data determined the need to organize five expeditions to Dagestan from 2020 to 2024. The results of the expeditions revealed a high spatial heterogeneity of rural development in the region. The presence of vast mountainous and the specifics of post-Soviet modernization of society and economy determine a particular nature of development of rural Dagestan. The classification procedure allowed identifying 10 types of districts in rural Dagestan with significant differences in their basic characteristics. The analysis of the dynamics of the main socio-economic indicators of Dagestan rural areas within different geographical, social, and economic types emphasized that a comprehensive analysis of the transformation of mountain territories should consider both the specific features of mountains and the factors of population and economy modernization. The study has shown that rural Dagestan has two main trajectories of socio-economic transformation of territories in the post-Soviet period, i.e., inertial and modernization. Together they demonstrate matching of such processes as the archaization and modernization of the local economy structure, and traditionalization and modernization of the society. It has been revealed that the inertial trajectory of rural transformation dominates in mountainous and piedmont rural areas, while the modernization one dominates in the plains. This is a serious challenge for the spatial development of the region.